Can You Fool Me? Towards Automatically Checking Protocol Gullibility - Stanojevic, Milan; Mahajan, Ratul; Millstein, Todd; Musuvathi, Madan (in HotNets '08, Seventh ACM Workship on Hot Topics in Networks, 2008)
We consider the task of automatically evaluating protocol gullibility, that is, the ability of some of the participants to subvert the protocol without the knowledge of the others. We explain how this problem can be formalized as a game between honest and manipulative participants. We identify the challenges underlying this problem and outline several techniques to address them. Finally, we describe the design of a preliminary prototype for checking protocol gullibility and show that it can uncover vulnerabilities in the ECN protocol.